Konstruksi Aplikatif Bahasa Indonesia - Nurhayati Sitorus; Mulyadi Mulyadi (Magister Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2022)
This research has the purpose of identifying and investigating the applicative constructions of Indonesian. The research conducted a descriptive qualitative method. Data were obtained from utterances and research books and the data from other authors that have been acknowledged to be true. Data collection was carried out by observation, such as notes and library research. The agih method was used to analyse the data. The technique applied in this research were techniques for direct elements, advanced techniques like vanishing techniques, insertion techniques, reverse techniques, expansion techniques, replacement techniques, and transformation techniques. In this case, the techniques applied were based on the author's needs. The study's results indicated that the benefactive applicative construction of Indonesian refers to the application of the Indonesian language, which was marked by the suffixes –kan and –i. Furthermore, instrumental applicative construction is an application process marked by the suffix –kan attached to the verb and indirect objects marked with the preposition